Potential utilization of seaweed-derived fusion salt in human diet - Bhagirath Rakhasiya; Adusumilli Somya; Aswin Alichen; Digvijay Singh Yadav; Bhavik Kantilal Bhagiya; Jasmine V. Rajai; Sudheer Kumar Yannam; Abhiram Seth; Jitendra Kumar Singh; Tanmaye Seth; Vaibhav A. Mantri (Applied Food Research)
The potential use of seaweed-derived salt is well known. This salt is low in sodium. Incorporating for replacement of sodium chloride salt considerable health benefits like lowering hypertension, and reducing incidences of cardio-vascular diseases. An off- flavour odour and taste make it not so preferred in daily diet. The present study aimed at formulating fusion products of seaweed salt with black salt (kiln-fired salt), rock salt (halite deposit), and raw salt (freshly harvested from saltpan) in different proportions [25:75. 50:50, and 75:25-weight-to-weight ratio]. The favoured fusion product was seaweed salt: black salt (25:75), with a total antioxidant activity (TAC) (11.44 ± 1.46 μg g−1) and cupric reducing antioxidant capacity (CUPRAC) (45.75 ± 2.07 μg g−1). Further, mineral characterisation, electronic tongue and electronic nose analyses has been performed. The data were cross-validated through volunteer's attitude score by using 9-point hedonic scale on which seaweed salt:black salt (25:75) scored 5.94. Among the macro-elements, ‘Na’ was highest (70.66 ± 8.65 mg g−1) with Na-to-K ratio 4.26; whereas among the micro-elements, ‘Fe’ was highest (7.71 ± 0.73 mg 100 g−1). Arsenic and lead were below detectable levels while other heavy metals, namely Cr, Co, Cd, and Hg were within permissible limit. E-nose analysis revealed the presence of nine potential volatile compounds, while e-tongue analysis for saltiness, bitterness, umami, and sourness reported 8.40, 6.00, 4.60, and 5.30 on a scale of 10 respectively. Thus favoured product seaweed salt: black salt (25:75) seems preferred for consumption than pure seaweed salt.